Novel Approach to Handling Microfiber-Rich Dye Effluent for Sustainable Water Conservation - R. Dharmaraj; Alagar Karthick; G. K. Arunvivek; S. Gopikumar; V. Mohanavel; M. Ravichandran; Murugesan Bharani (Advances in Civil Engineering)
The replacement of substances that favor the manufacturing of utility blocks ingredients is unpredictable in modern research. The experimental approach structured for the present investigation considered partial substitution of the cement mantle of a concrete matrix with dried fly ash sediment powder. As exploring innovation in being treated, dye wastewater is used in place of precious potable water for preparing mix ratio. The experimental outcomes were strongly supported by a regression representation at a macrolevel analysis and a scanning electron microscopy analysis at a microstructural level. The correlation coefficient of the developed mathematical models exhibited a dependable correlation of more than 90%. This shows the reliability of the developed regression equation for base strength predictions. Accordingly, the eventual safer and optimal limit of proportioning such a foreign matter like the dried fly ash sediment powder usage is controlled, not exceeding 9% by weight of cement mantle. However, due to the infused sediment particles within the treated effluents, the potable water is 100% replaced without sacrificing the basic quality. The administration of this dye effluent in artificially constructed wetland methods is designed for sustainable water conservation.